Multimedia Interaktif Pengenalan Museum Bali - Rahayu Widasari, Made Bandem Yosita; Sudana, Anak Agung Kompiang Oka; Wiranatha, Agung Agung Ketut Cahyawan (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 3 No 2 (2022): JITTER, Vol.3, No.2, August 2022, 2022)
Abstract Museum nowadays is not just a place for preserving historical objects, but also become a place of recreation and education. Bali Museum, located in Denpasar, Bali, is one of many museums that has collection more than 2500 pieces, most of them consist of ethnographic, Numismatic, and Archeological collection, The implementation of interactive multimedia for introducing Bali Museum as an innovation is made to help increase tourist attraction and also make it easier for tourists to obtain important information related to Balinese history packaged in an interesting and informative way. This interactive multimedia is made using Visual Basic and later will be displayed on a screen like queue machine which expected to make it easier for visitor. The expected result is this interactive can attract more tourists and make it easier for tourists to get know about the museum before entering the rooms in the museum.